2018
DOI: 10.3390/su11010041
|View full text |Cite
|
Sign up to set email alerts
|

Can China’s Agricultural FDI in Developing Countries Achieve a Win-Win Goal?—Enlightenment from the Literature

Abstract: Since 2014, there have been increasing numbers of undernourished people in the world, mainly distributed in developing countries. At the same time, the rapid growth of China's agricultural FDI (Foreign Direct Investment) has attracted international attention. There are different opinions on whether China's fast-growing agricultural investment can contribute to promoting global food security. The objective of the article is to clarify the consensus and differences of current research, and explore the actual imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
(109 reference statements)
1
25
0
Order By: Relevance
“…Chinese companies are increasing their investments in foreign agricultural and food assets. Their broad aims are to gain profits for Chinese investors while achieving national food security and projecting China's influence abroad (Jiang et al, 2018). China's agricultural foreign direct investment (FDI) is concentrated in developed countries such as Singapore, New Zealand, the United States, Australia (Raymond et al, 2018) and Asian developing countries, one of these places is Russian Far East (RFE) (Buckley, 2019).…”
Section: Introduce the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese companies are increasing their investments in foreign agricultural and food assets. Their broad aims are to gain profits for Chinese investors while achieving national food security and projecting China's influence abroad (Jiang et al, 2018). China's agricultural foreign direct investment (FDI) is concentrated in developed countries such as Singapore, New Zealand, the United States, Australia (Raymond et al, 2018) and Asian developing countries, one of these places is Russian Far East (RFE) (Buckley, 2019).…”
Section: Introduce the Problemmentioning
confidence: 99%
“…The author claims that Chinese workers in the RFE not only fill a labour shortage, but also contribute positively to local food security, with negative impacts being more socially normative and political, than economic. Jiang et al (2018) suggested that more on-the-spot investigations and investment project evaluations are needed to study the investment cooperation model that suits the interests of both parties in order to achieve a win-win goal. The three RFE's regions considered in this article are in the top 10 regions producing soybeans in Russia: they accounted for 38.6% of Russia's soybean production in 2018.…”
Section: Introduce the Problemmentioning
confidence: 99%
“…For the host country, some studies consider investment in overseas farmland as a kind of "land grab" [7,8], and indicate that the rights of farmers in the host country are not effectively protected [8]. However, the Food and Agriculture Organization of the United Nations (FAO) reports indicate that overseas arable land investment is actually a kind of transnational investment [9], and other studies conclude that overseas arable land investment brings employment opportunities to farmers [10], and improves agricultural output levels by sharing agricultural science and technology in underdeveloped areas [6,11]. Although there are both supporters and opponents of investment in overseas farmland, as a developing country with poor arable land resources China's investment in overseas arable land has attracted great attention from international researchers [7, [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…China's Ministries of Finance and Commerce jointly issued documents and notices giving financial support to overseas enterprises and investment-oriented Chinese enterprises [9]. In 2013, for the first time, the scale of China's investment in foreign agriculture exceeded the scale of investment by foreign entities in Chinese agriculture [10][11][12]. As part of its agricultural investment, China's investment in overseas arable land is expected to accelerate due to the country's "Belt and Road" initiative and the continuous increase in China's comprehensive national power [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation